Follicular Keratosis in Adolescents: Diagnostic Features and Cosmetological Aspects of Therapy - Evgenia V. Ikonnikova; Larisa S. Kruglova ("Paediatrician" Publishers LLC, 2022)
Follicular keratosis (FK) is one of the most common dermatological diseases in children. FK manifests usually in early childhood and worsen frequently, thus, symptoms are more prominent during puberty. The skin of proximal extensors of upper and lower limbs is mainly affected, while skin of cheeks, back and buttocks is affected more rarely. FK is just a cosmetic defect which significantly affects adolescents' self-esteem and emotional state up to the development of severe depressive syndrome and obsessive conditions accompanied by pathomimia. FK can be associated with other nosologies such as: atopic dermatitis, vulgar ichthyosis, obesity, diabetes mellitus, and even aggravate Down and Noonan syndromes. Spontaneous improvement is still possible with age. We can use topical therapy with emollient, keratolytic, anti-inflammatory drugs, as well as various types of laser and phototherapy to alleviate the disease symptoms. This article provides basic information on etiology, pathogenesis, and treatment of FK with clinical case description.